Sistem Tanda dan Makna Simbolik sebagai Unsur Gaya Kepengarangan dalam Antologi Puisi Perjamuan Khong Guan Karya Joko Pinurbo - Nadeak, Jesika; Warni, Warni; Wulandari, Sovia (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
This research aims to describe the sign system and symbolic meaning as elements of authorial style in the poetry anthology book Perjamuan Khong Guan by Joko Pinurbo. The authorial style in question is based on elements of poetry which become a system of signs and symbolic meaning. This type of research is qualitative with data in the form of words, phrases, sentences, or paragraphs or narratives that contain a system of signs and symbolic meaning. The data source in this research is the poetry anthology Khong Guan Supper by Joko Pinurbo. The method used in the research is descriptive qualitative, data collection was carried out by literature study using reading and note-taking techniques. The results of the research were that 30 poems were obtained as data, including two poems whose meaning was based on words, two poems whose meaning was based on typography, and 26 poems whose meaning was based on sentences. These three elements are elements that form poetry which are used as the basis for meaning in poetry. These forming elements are also seen as Joko Pinurbo's authorial style. The system of signs and symbolic meanings contained in the anthology Khong Guan Banquet by Joko Pinurbo in this research is used as a reference to reveal Joko Pinurbo's authorial style. The signs in question are sounds, words, sentences, and typography or appearance. However, in this research, there is no sound as a sign system so what is obtained is only three aspects such as words, sentences, and typography. The conclusion of this research can be seen from the three aspects that form poetry which are stated as signs because they are the center of meaning in a poem and can provide aesthetic value in poetry so that we can see that Joko Pinurbo's authorial style in terms of the sign and meaning system is classified into three types, namely: 1) style that relies on words, 2) style that relies on sentences, 3) style that relies on typography or appearance. Abstrak Penelitian ini bertujuan untuk mendeskripsikan sistem tanda dan makna simbolik sebagai unsur gaya kepengarangan dalam buku antologi puisi Perjamuan Khong Guan karya Joko Pinurbo. Gaya kepengarangan yang dimaksud ialah bertumpu pada unsur puisi yang menjadi sistem tanda dan makna simbolik. Jenis penelitian adalah kualitatif dengan data berupa kata, frasa, kalimat, maupun paragraf atau narasi yang mengandung sistem tanda dan makna simbolik. Sumber data dalam penelitian ini ialah antologi puisi Perjamuan Khong Guan karya Joko Pinurbo. Metode yang digunakan dalam penelitian yakni deskriptif kualitatif, pengumpulan data dilakukan dengan studi pustaka menggunakan teknik baca dan catat. Hasil penelitian yaitu didapatkan 30 puisi sebagai data, diantaranya ialah dua puisi yang maknanya bertumpu pada kata, dua puisi yang maknanya bertumpu pada tipografi, dan 26 puisi yang maknanya bertumpu pada kalimat. Ketiga unsur tersebut ialah unsur pembentuk puisi yang dijadikan sebagai tumpuan makna dalam puisi. Unsur pembentuk tersebut pulalah yang dilihat sebagai gaya kepengarangan Joko Pinurbo. Sistem tanda dan makna simbolik yang terdapat pada antologi Perjamuan Khong Guan karya Joko Pinurbo dalam penellitian ini dijadikan sebagai acuan untuk mengungkapkan gaya kepengarangan Joko Pinurbo. Tanda-tanda yang dimaksud ialah bunyi, kata, kalimat, dan tipografi atau perwajahan. Namun dalam penelitian ini, tidak terdapat bunyi sebagai sistem tanda sehingga yang didapatkan hanyalah ketiga aspek seperti kata, kalimat, dan tipografi. Kesimpulan dari penelitian ini dapat dilihat dari ketiga aspek pembentuk puisi yang dinyatakan sebagai tanda karena menjadi pusat makna dalam suatu puisi serta dapat memberikan nilai estetis dalam puisi sehingga dapat kita lihat bahwa gaya kepengarangan Joko Pinurbo yang ditinjau dari sitem tanda dan makna diklasifikasikan menjadi tiga jenis yaitu: 1) gaya yang bertumpu pada kata, 2) gaya yang berttumpu pada kalimat, 3) gaya yang bertumpu pada tipografi atau perwajahan.